A Physicochemical Study to Evaluate the Subsistence of Inclusion Complexes of Cyclodextrins with 1-Butyl-2, 3-dimethylimidazolium Tetrafluoroborate Probe - Sarkar, Kalipada; Roy, Debadrita; Barman, Sanjoy; Saha , Baishali; Barman, Siti; Roy, Mahendra Nath (Current Topics on Chemistry and Biochemistry Vol. 2, 2022)
Ionic liquids (ILs) are nonvolatile, nonflammable and thermally stable solvents. They are termed green solvents since they do not harm the environment. In aqueous medium, Inclusion complexes of ionic liquid, 1-butyl-2,3-dimethylimidazolium tetrafluoroborate (BDMImBF4) into cavity of hollow cylinder oligosaccharide, \(\boldsymbol{α}\)- and \(\boldsymbol{β}\)-cyclodextrins are manifested. Surface tension and conductance experiments verify the stoichiometry of interfacial inclusion, while IR and 1HNMR spectroscopy confirm the inclusion phenomena. Volumetric and viscometric tests are used to analyze the interaction between cyclodextrin and ionic liquid.